Hubungan Usia, Paritas, Penyakit Infeksi Dan Status Gizi Ibu Terhadap Kejadian Kelainan Kongenital Mayor pada Janin - Zahra Dewi Hasna Difa; Khairun Nisa; Betta Kurniawan; Nurul Islamy; Rodiani - (CV. Jasa Sukses Abadi, 2023)
Major congenital abnormalities refer to medical and cosmetic abnormalities that require surgery and are a leading cause of mortality among children under the age of five in Indonesia. Several risk factors contribute to congenital abnormalities, including the mother’s age, parity, infectious diseases, nutritional status, environment, education, and employment. This study aims to determine the relationship between age, parity, infectious diseases, and nutritional status of mothers and the occurrence of major congenital abnormalities. Secondary data from medical records of mothers who received treatment in the delima room at RSUD Dr. H. Abdul Moeloek were analyzed using an observational analytic method and a cross-sectional approach. The chi-square test and odds ratio values were used to test the major congenital abnormalities' relationship with the risk factors. Results showed that there was a significant association between nutritional status, infectious diseases, and parity with the incidence of major congenital abnormalities (p = 0,004; OR = 0,086; 95% CI = 0,016-0,468), (p = 0,034; OR = 6,816; 95% CI = 1,288 – 36,062) and (p = 0,005; OR = 9,567; 95% CI = 1,549 – 30,206), but not with maternal age (p = 0,724; OR = 1,333; 95% CI = 0,322 – 5,526). The incidence of major congenital abnormalities is related to nutritional status, infectious diseases, and parity, but not to maternal age.